2018
DOI: 10.1097/ccm.0000000000003383
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Storage Age of Blood in Massively Transfused Burn Patients: A Secondary Analysis of the Randomized Transfusion Requirement in Burn Care Evaluation Study

Abstract: Objective: Major trials examining storage age of blood transfused to critically-ill patients administered relatively few blood transfusions. We sought to determine if the storage age of blood affects outcomes when very large amounts of blood are transfused. Design: A secondary analysis of the multicenter randomized Transfusion Requirement in Burn Care Evaluation (TRIBE) study which compared restrictive and liberal transfusion strategies. Setting: Eighteen tertiary-care burn centers. Patients: TRIBE evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Current evidence on critically ill trauma (4), burn (5), and cardiac surgery (6) might not apply to surgical patients as they may have a different risk profile (7). Specifically, anemia in surgical critically ill patients is multifactorial: surgical blood loss, cytokines inhibition of erythropoiesis, coagulopathy, hemodilution in the context of volume administration, and iatrogenic from diagnostic phlebotomies (8).…”
mentioning
confidence: 99%
“…Current evidence on critically ill trauma (4), burn (5), and cardiac surgery (6) might not apply to surgical patients as they may have a different risk profile (7). Specifically, anemia in surgical critically ill patients is multifactorial: surgical blood loss, cytokines inhibition of erythropoiesis, coagulopathy, hemodilution in the context of volume administration, and iatrogenic from diagnostic phlebotomies (8).…”
mentioning
confidence: 99%
“…Additionally, it further validates the findings of the ABLE study with greater extrapolation potential. Although similar outcomes have been found in randomized trials in the burn (15), trauma (16), and cardiac surgical patients (17), the study by Lehr et al (11) provides an application to those requiring intensive care after a broader array of surgical interventions. These findings should help alleviate the concern with triaging RBC transfusions in surgical ICU patients based upon the storage age.…”
mentioning
confidence: 67%
“…9 of 11 worsened outcomes came from four single‐center studies, 14–16,18 three of which were from the same institution 14,16,18 . In contrast, the multi‐center studies collectively measured eight mortality and morbidity outcomes, yet found only a single worsened morbidity outcome 3,11–13,17 . An unrelated systematic review of 12 meta‐analyses found single‐center studies overestimate treatment effects compared with multi‐center studies.…”
Section: Limitations In the Reviewed Studiesmentioning
confidence: 99%
“…Six found no association between RBCs ≥35 days old and increased mortality. 3,11,12,14,17,18 Eikelboom and colleagues retrospectively reviewed cardiovascular acute care patients at a single center in Canada and found a modest mortality association following transfusion with at least one unit of RBCs stored ≥35 days compared with 7-14 days. They noted a "continuous and graded" increase in mortality with increasing RBC age, not a large jump in the final week.…”
Section: Mortality Outcomesmentioning
confidence: 99%
See 1 more Smart Citation